Can animals be moral - Rowlands, Mark. (New York ; Oxford : Oxford University Press, 2013)
Building on the ethological evidence, this book engages in meticulous philosophical analysis and argument, and decides that animals can indeed be moral. Animals can act morally in the sense they can act for moral reasons. Or, at least, they are no compelling logical obstacles to supposing that this is the case. This conclusion has important implications not just for our understanding of animals but also of the central concepts we employ in understanding the moral lives of humans, such as motivation, action, and agency.
Description based on online resource; title from PDF title page (viewed on Oct. 31, 2012).
Includes index.
Keywords: Ethics -- History; Animals (Philosophy); Emotions in animals; Animal psychology